2010
DOI: 10.1143/jpsj.79.074708
|View full text |Cite
|
Sign up to set email alerts
|

DC Current Driven Critical Current Variation in Sr2RuO4–Ru Junction Proved by Local Transport Measurements

Abstract: To search for new evidence of the chiral p-wave superconducting domain in Sr2RuO4, we investigated the unconventional local transport characteristics of a microfabricated Sr2RuO4-Ru eutectic junction. We found that the anomalous hysteresis in voltage-current characteristics [as reported in H. Kambara et al.: Phys. Rev. Lett. 101 (2008) 267003.] is strongly affected by dc currents, but not by magnetic fields. This suggests that dc current acts as a driving force to move chiral p-wave domain walls; a domain wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…The domain size is almost consistent with those estimated by several results using the 3-K phase [25][26][27], while it is somewhat larger than ∼1 µm estimated by Kidwingira et al [19]. We speculate that the relatively larger domain can be induced by s-wave Nb films whose superconducting transition temperature T c (∼6.5 K) is higher than that of SRO.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The domain size is almost consistent with those estimated by several results using the 3-K phase [25][26][27], while it is somewhat larger than ∼1 µm estimated by Kidwingira et al [19]. We speculate that the relatively larger domain can be induced by s-wave Nb films whose superconducting transition temperature T c (∼6.5 K) is higher than that of SRO.…”
supporting
confidence: 91%
“…We note that the IS is insensitive to the junction dimension, λ J , and the uniformity of the current. According to the previous experiments, chiral domain wall motion is considered to be excited by applied magnetic fields [19] or by a current flow [25][26][27]. Here, we aim to test the domain wall motion by reducing the junction dimension.…”
mentioning
confidence: 99%
“…It was interpreted as due to the motion of the chiral domain walls which alters the critical current. [222][223][224] As a novel phenomenon ascribable to real-spatial topology of chiral superconductivity, the critical current of a junction between Sr 2 RuO 4 and the s-wave superconductor Pb has been investigated. 225) Pb/Ru/Sr 2 RuO 4 proximityjunctions (Fig.…”
Section: Sr 2 Ruo 4 As a Topological Superconductormentioning
confidence: 99%
“…As a result, two chiral domains are naturally separated by a chiral domain wall (chiral-DW), like ferromagnetic domain walls in a ferromagnetic material. Recently, the existence of chiral-DWs and its dynamic behavior has been investigated experimentally and theoretically 11,[19][20][21][22][23][24][25][26] . Kindwingra et al 19 , reported complicated and hysteretic diffraction patterns in Pb/Cu/SRO junctions.…”
Section: Introductionmentioning
confidence: 99%